Single-cell transcriptomic construction of fibroblast score for analysis of immune infiltration in primary and metastatic ovarian cancer - Guo, Qian; Ding, Hongmei; Zheng, Qinlin (Frontiers in Genetics, 2025)
PurposeOvarian cancer (OV) is a malignant gynecologic cancer with poor clinical outcomes and poor prognosis. The aim of this study was to explore the immune infiltration between primary and metastatic ovarian cancer and the function of fibroblast differential marker in ovarian cancer immunomodulation.MethodsObtained single-cell transcriptome datasets of primary ovarian cancer and metastatic ovarian cancer, performed cell communication analysis and enrichment analysis. Constructed a new fibroblast score, constructed a prognostic model, screened for prognostically relevant fibroblast differential markers, and analyzed the role of differential markers in immune infiltration of ligand-receptor cells.ResultsSingle-cell data analysis of ovarian cancer revealed the existence of intercellular communication between fibroblasts and mononuclear macrophages. COX one-way analysis of 28 differential genes in ovarian cancer fibroblasts yielded five genes with prognostic significance for ovarian cancer, and a new Fib score constructed on the basis of these five genes accurately predicted the prognosis of ovarian cancer patients. Further analysis of these five genes revealed that TIMP3 in ovarian cancer fibroblasts affected tumor prognosis, immunosuppression, and drug resistance by targeting M2-type macrophages through the regulation of the CXCL12/CXCR4 signaling axis, which was specifically shown that the higher the expression of TIMP3, the worse the prognosis, the more significant the immune infiltration, and the more drug-resistant the ovarian cancer was.ConclusionIn metastatic ovarian cancer, fibroblasts induce macrophage polarization through the TIMP3-regulated CXCL signaling pathway, which affects the prognosis of ovarian cancer patients and drug resistance of ovarian cancer cells.